Rakstveida process administratīvajā tiesā - Kārkle, Inese (Latvijas Universitāte, 2009)
2004.gada 1.februārī Latvijā stājās spēkā ,,Administratīvā procesa likums’’, kas paredzēja, ka administratīvās lietas izskatīšana tiesā ir iespējama ne tikai mutvārdu procesā, bet arī rakstveida procesā. Rakstveida procesā lietas apstākļi tiek noskaidroti bez lietas izskatīšanas tiesas sēdē, atbilstoši Administratīvā procesa likuma 206. panta otrajai daļai. Tiesnesim rakstveida procesā nav jāpieņem lēmums, kurā nosaka tiesas sēdes dienu, laiku un uz tiesu aicināmās un izsaucamās personas. Šāds rakstveida process administratīvajā tiesās procesā ir daudz ātrāks un efektīvāks, jo tādā veidā paver iespējas privātpersonai uz lietas ātrāku izskatīšanu. Īpaši svarīgi tas ir gadījumos, kad privātpersona ir ieinteresēta pēc iespējas ātrākā konkrētās lietas izspriešanā. Bakalaura darbs sastāv no trim nodaļām, rakstveida un mutvārdu procesa salīdzinājums administratīvajā tiesā, priekšnoteikumi lietas izskatīšanai un procesa dalībnieku viedokļu noskaidrošana rakstveida procesā, rakstveida process nākamajās tiesu instancēs, blakus sūdzības un citu procesuālo jautājumu izskatīšana.

The article is dedicated to the procedural aspects of administrative court hearing when a written procedure has been determined. The article considers taking into account the recent amendments made to the Law on Administrative Procedure that aim to unburden the use of written procedure in administrative court and focuses on the analysis of the European Court of Humans Rights decision. Introductory part of the article focuses on the analysis of the substance of oral and written procedures in administrative court and main distinction between the both. At first author continues her reasoning uncovering the preconditions for the written procedure to be implemented in administrative court hearing, and the written procedures before the ensuing court instances, taking into account that a court may adjudge a meter without a court sitting if the documents in the matter are sufficient and the participants in the administrative proceeding have consented thereto in writing. The specific aspects of development and substance of judgment in written procedure are analyzed henceforth, as well as procedure of ancillary complaint and other procedural matter resolution in case a written procedure has been determined for the main hearing. And points out that the key objective of written procedure to be implemented in administrative court hearings to expedite the case and make it more efficient, especially due to the reason that individual is interested to achieve result out of his dispute with the public authority as soon as possible. Author draws attention to the fact that court hearing in a written procedure does not provoke the case to be heard differently by its substance as it would be heard in an oral procedure. Finally, it is considered that the main impediment for the written procedure to be implemented in an administrative court more and more frequently is distrustfulness of an individual in this form of procedure due to the fact that individual does not directly participate in the court hearing.
Written procedure in administrative court
Keywords: Juridiskā zinātne